Muscle Precursor Cells Enhance Functional Muscle Recovery and Show Synergistic Effects With Postinjury Treadmill Exercise in a Muscle Injury Model in Rats. Issue 4 (March 2021) - Contreras-Muñoz, Paola; Torrella, Joan Ramón; Venegas, Vanessa; Serres, Xavier; Vidal, Laura; Vila, Ingrid; Lahtinen, Ilmari; Martínez-Ibáñez, Vicente; Peiró, José Luis; Järvinen, Tero A.H.; Rodas, Gil; Marotta, Mario
Background: Skeletal muscle injuries represent a major concern in sports medicine. Cell therapy has emerged as a promising therapeutic strategy for muscle injuries, although the preclinical data are still inconclusive and the potential clinical use of cell therapy has not yet been established. Purpose: To evaluate the effects of muscle precursor cells (MPCs) on muscle healing in a small animal model. Study Design: Controlled laboratory study. Methods: A total of 27 rats were used in the study. MPCs were isolated from rat (n = 3) medial gastrocnemius muscles and expanded in primary culture. Skeletal muscle injury was induced in 24 rats, and the animals were assigned to 3 groups. At 36 hours after injury, animals received treatment based on a single ultrasound-guided MPC (10 5 cells) injection (Cells group) or MPC injection in combination with 2 weeks of daily exercise training (Cells+Exercise group). Animals receiving intramuscular vehicle injection were used as controls (Vehicle group). Muscle force was determined 2 weeks after muscle injury, and muscles were collected for histological and immunofluorescence evaluation. Results: Red fluorescence–labeled MPCs were successfully transplanted in the site of the injury by ultrasound-guided injection and were localized in the injured area after 2 weeks. Transplanted MPCs participated in the formation of regenerating muscle fibers as corroborated by the co-localization of red fluorescence with developmental myosin heavy chain (dMHC)–positive myofibers by immunofluorescence analysis. A strong beneficial effect on muscle force recovery was detected in the Cells and Cells+Exercise groups (102.6% ± 4.0% and 101.5% ± 8.5% of maximum tetanus force of the injured vs healthy contralateral muscle, respectively) compared with the Vehicle group (78.2% ± 5.1%). Both Cells and Cells+Exercise treatments stimulated the growth of newly formed regenerating muscles fibers, as determined by the increase in myofiber cross-sectional area (612.3 ± 21.4 µm 2 and 686.0 ± 11.6 µm 2, respectively) compared with the Vehicle group (247.5 ± 10.7 µm 2 ), which was accompanied by a significant reduction of intramuscular fibrosis in Cells and Cells+Exercise treated animals (24.2% ± 1.3% and 26.0% ± 1.9% of collagen type I deposition, respectively) with respect to control animals (40.9% ± 4.1% in the Vehicle group). MPC treatment induced a robust acceleration of the muscle healing process as demonstrated by the decreased number of dMHC-positive regenerating myofibers (enhanced replacement of developmental myosin isoform by mature myosin isoforms) (4.3% ± 2.6% and 4.1% ± 1.5% in the Cells and Cells+Exercise groups, respectively) compared with the Vehicle group (14.8% ± 13.9%). Conclusion: Single intramuscular administration of MPCs improved histological outcome and force recovery of the injured skeletal muscle in a rat injury model that imitates sports-related muscle injuries. Cell therapy showed a synergistic effect when combined with an early active rehabilitation protocol in rats, which suggests that a combination of treatments can generate novel therapeutic strategies for the treatment of human skeletal muscle injuries. Clinical Relevance: Our study demonstrates the strong beneficial effect of MPC transplant and the synergistic effect when the cell therapy is combined with an early active rehabilitation protocol for muscle recovery in rats; this finding opens new avenues for the development of effective therapeutic strategies for muscle healing and clinical trials in athletes undergoing MPC transplant and rehabilitation protocols.